1999 International Special Merit Award for Community - B. Alex White, DDS, DrPH (Blackwell Synergy, 2000)
International members are important to our association’s future and to continued improvement in the health and oral health of the public. To recognize the valuable contributions of our international colleagues, AAPHD established the International Special Merit Award for Community Dentistry. It is indeed an honor to present this year’s award to Dr. Mario Chaves.